Performance characteristics of stroke patients using the motor activity log and ANOVA analysis - Norsahperi, Nor Mohd Haziq; Abd Mutalib, Mohd Azri; Azlan, Norsinnira Zainul; Hassan, Hafizu Ibrahim (Universiti Malaysia Pahang Al-Sultan Abdullah Publishing, 2024)
Scoring system is crucial in evaluating a patient’s stroke severity and monitoring their recovery progress. The current manual and subjective approach heavily rely on the therapist’s individual expert, resulting inconsistent in scores and increased burden on the therapist’s workload. This pilot study aims to automate and refine the scoring methodology utilised for stroke patient’s assessment. This study focuses on Motor Activity Log (MAL), a widely acknowledged standard clinical assessment that incorporatesthe evaluation of Activities of Daily Living (ADL) in stroke patients. Data are collected from 30 healthy individuals and 30 stroke patients. Two statistical analyses using one-way ANOVA are performed to check the data characteristics and assess the effectiveness of the MAL in this context. The analysis results indicated two scores that did not show significant differences, specifically 0.328 for the Rotation X parameter in the Doorknob activity and 0.587 for the Time parameter in the Water Faucet activity. This demonstrates that this test method can effectively differentiate between each stroke patient. This initiative represents a significant step towards establishing a more standardised and objective scoring system, contributing to a more consistent and efficient evaluation of stroke patients' performance characteristics and recovery trajectories.